(untitled) (Research, Society and Development, 2022)
Introduction: Despite the publication of evidence-based good practices recommended by the Ministry of Health and the World Health Organization, the process of childbirth has still been assisted based on hospital habits focused on the rational labor process. General Objective: To identify the practices of labor, delivery and immediate postpartum care, practiced in institutions in the state of Rio de Janeiro. Methodology: This is a quantitative field research, with women who gave birth in the state of Rio de Janeiro, from January 2018 to March 2022, in health institutions. Data collection was via Microsoft Forms, distributed by the WhatsApp application. Results: 47 women participated in the research. 72.3% gave birth in the SUS. 51.06% are brown and black. 59.6% did not receive information in prenatal care about non-pharmacological labor pain relief techniques, but 55.3% had access to non-traditional pain relief methods. 70.2% were not fed during labor, and 61.7% delivered in the lithotomy position. 48.1% felt welcomed by the nursing staff. 59.6% were informed about the advantages of skin-to-skin contact and breastfeeding in the delivery room during prenatal care, 51.1% had skin-to-skin contact for up to 30 minutes, and 21.3% for up to 1 hour. Conclusion: Obstetric care in the sample represented by the study partially meets evidence-based recommendations. And nursing plays an important role in building women’s autonomy throughout the perinatal period.